Nutritional composition and potential utilization of Parquetina nigrescens and Morinda lucida: comparative evaluation of whole, residue and coagulum fraction - Akinyemi , B. Temitope; Apalowo, I. Gideon; Yusuf, A. Olanrewaju; Dele , P. Aniwe (ADAN JOURNAL OF AGRICULTURE, 2026)
Seasonal feed scarcity and declining forage quality in tropical regions severely limit ruminant productivity, necessitating evaluation of alternative underexploited plant protein sources. This study investigated the nutritional composition and potential feed utilization of Parquetina nigrescens and Morinda lucida through a comparative assessment of their leaf protein concentrate fractions. Fresh leaves of Parquetina nigrescens and Morinda lucida were collected, chopped, milled and processed into three (3) form (whole, residue and coagulum). A 2 × 3 factorial experiment was conducted to determine the effects of plant species and leaf protein concentrate form on proximate composition, mineral concentration, and anti-nutritional constituents. The results revealed significant (P < 0.05) differences across species and processing fractions. The coagulum fraction of both plants exhibited markedly higher crude protein contents (40.36%) in P. nigrescens and (38.04%) in M. lucida, compared to the residue fractions (18.16%) while, Neutral Detergent Fibre, Acid Detergent Fibre, Acid Detergent Lignin were lowest in coagulum samples with (26.05%), (24.68%) and (4.73%) respectively. Morinda lucida coagulum showed higher Calcium (31.49 mg/kg) and Potassium (40.53 mg/kg). Anti-nutritional factors were generally higher, which were tannin (0.28%), alkaloid (0.72%) and saponin (0.18%) in P. nigrenscens whole form. The findings highlight the potential of these shrubs, particularly their coagulum fractions as natural protein and mineral sources that can enhance the nutritional quality of tropical forages and promote sustainable livestock feeding systems.